How Might Recharge Change Under Projected Climate Change in the Western U.S.?. Issue 20 (30th October 2017) - Niraula, R.; Meixner, T.; Dominguez, F.; Bhattarai, N.; Rodell, M.; Ajami, H.; Gochis, D.; Castro, C.
Abstract: Although groundwater is a major water resource in the western U.S., little research has been done on the impacts of climate change on groundwater storage and recharge in the West. Here we assess the impact of projected changes in climate on groundwater recharge in the near (2021–2050) and far (2071–2100) future across the western U.S. Variable Infiltration Capacity model was run with RCP 6.0 forcing from 11 global climate models and "subsurface runoff" output was considered as recharge. Recharge is expected to decrease in the West (−5.8 ± 14.3%) and Southwest (−4.0 ± 6.7%) regions in the near future and in the South region (−9.5 ± 24.3%) in the far future. The Northern Rockies region is expected to get more recharge in the near (+5.3 ± 9.2%) and far (+11.8 ± 12.3%) future. Overall, southern portions of the western U.S. are expected to get less recharge in the future and northern portions will get more. Climate change interacts with land surface properties to affect the amount of recharge that occurs in the future. Effects on recharge due to change in vegetation response from projected changes in climate and CO2 concentration, though important, are not considered in this study. Key Points: Climate change interacts with land surface properties to affect the amount of recharge that occurs in the future Southern portions of the western U.S. are expected to get less and northern portions more recharge in the future The large variability in projected recharge across the GCMs is associated with variability in projected precipitation